Evaluation of a novel dipotassium phosphate bolus for treatment of metabolic disorders in dairy cattle - Verhoef, Walter; Zuidhof, Sjoert; Ross, Joseph A.; Beaugrand, Kendall; Olson, Merle (Frontiers in Veterinary Science, 2023)
A dipotassium phosphate bolus (KPhos-Boost) has been developed to treat both hypophosphatemia and hypokalemia, as the clinical signs of both conditions are similar and occur in the early postpartum period. The objective of this research was to evaluate the efficacy of the bolus for prevention and treatment of the common metabolic diseases in dairy production systems. Study 1 (Pharmacokinetics): Healthy post-partum cows were either untreated or received two KPhos-Boost boluses at times 0, 24, and 48 hours. Blood was taken at t=0, 2-, 4-, 6-, 8-, 10-, 24-, and 52-hours post-treatment for analysis of total serum minerals. There was an increase in serum phosphorous to normal levels within 2 hours of treatment with the bolus, but control cows remained hypophosphatemic. Serum potassium was significantly elevated 2 hours after bolus administration relative to control, while calcium, magnesium, sodium, and chloride levels were not affected by the KPhos-Boost bolus. Study 2 (Downer Cow Treatment): KPhos-Boost boluses were provided to cows that were unresponsive to intravenous calcium therapy and had been unable to stand for over 24 hours ("downer cows"). Most cows (16 of 19) treated with two boluses were standing without assistance between 1 and 24 hours after treatment and the serum phosphorous was increased to normal levels in 5 of 5 tested animals. Study 3 (Ketosis Treatment): Cows with clinical ketosis were provided with propylene glycol and KPhos-Boost boluses (n=29) or only propylene glycol (n=23). Cows treated with the KPhos-Boost bolus showed a more rapid recovery by increased milk production (3.9 kg/day) and rumination rate (97 min/day). Study 4 (Health Promotion): Cows in herds with >40% post-partum hypophosphatemia received KPhos-Boost boluses (n=130) or no treatment (n=146) following calving. There was a trend for treated 2nd-lactation animals to have higher milk production after 30 DIM (49.1 vs 46.2 kg/day; P=0.09). There were no significant differences between control and bolus treated animals in the incidence of subclinical ketosis, postcalving total health events, or culling rates. The studies described in this paper are early investigations and further research should be conducted to demonstrate the applications of a dipotassium phosphate bolus in dairy cows.